Utilization of d-Ribose by Veillonella - Kafkewitz, David (1969)
Three strains of Veillonella, representing two species, were unable to utilize carbohydrates as energy sources for growth. Ribose, however, was utilized biosynthetically by all three strains. Exponentially growing cultures removed (14)C-ribose from the growth medium and retained radioactivity throughout the growth cycle. The kinetics of removal of ribose from the growth medium was found to depend on the initial ribose concentration. Uptake by resting cells was found to require active metabolism, was greatly stimulated by the presence of an energy source, and was insensitive to the presence of other pentoses. Fractionation of cells showed that the ribose was used for synthesis of acid-precipitable material, with as much as 92% of the radioactivity being found in the nucleic acid fraction. The intracellular distribution of ribose radioactivity did not change during growth after uptake was completed.